2021
DOI: 10.3389/feduc.2021.699785
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns of Teachers’ Occupational Well-Being During the COVID-19 Pandemic: Relations to Experiences of Exhaustion, Recovery, and Interactional Styles of Teaching

Abstract: This study examined profiles of teachers’ occupational well-being during the COVID-19 pandemic. The data were collected from 279 Finnish primary school teachers during the spring of 2020. Four groups of teachers were identified by using Latent Profile Analysis: 1) teachers with mediocre stress and work engagement (34.4%); 2) teachers with mediocre stress and lowest work engagement (11.5%); 3) teachers with highest stress and work engagement (26.5%); and 4) teachers with lowest stress and highest work engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 60 publications
6
34
0
Order By: Relevance
“…It has been observed that teachers are often highly engaged in their work but, at the same time, there are rather worrying indications that teacher burnout is on the rise. As a result of the COVID-19 pandemic and the subsequent remote teaching and increased stress, teachers' well-being may have deteriorated further and burnout symptoms become even more common (see Pöysä et al, 2021;Salmela-Aro et al, 2020). Consequently, it seems increasingly crucial to explore the complex phenomenon of teacher well-being by investigating the simultaneously salient work engagement and burnout, and by examining its associations with factors possibly promoting teacher well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that teachers are often highly engaged in their work but, at the same time, there are rather worrying indications that teacher burnout is on the rise. As a result of the COVID-19 pandemic and the subsequent remote teaching and increased stress, teachers' well-being may have deteriorated further and burnout symptoms become even more common (see Pöysä et al, 2021;Salmela-Aro et al, 2020). Consequently, it seems increasingly crucial to explore the complex phenomenon of teacher well-being by investigating the simultaneously salient work engagement and burnout, and by examining its associations with factors possibly promoting teacher well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the engaged profile appears to be commonly recurrent, but the number of employees representing the profile varies somewhat between studies. Although we still have a fairly limited number of studies concerning teacher well-being during the COVID-19 pandemic, it may be that the number of engaged teachers has declined due to this unprecedented situation (see Pöysä et al, 2021;Salmela-Aro et al, 2020).…”
Section: Work Engagement and Burnout Profiles Among Teachersmentioning
confidence: 99%
“…This change in their work setting has led to heightened overload and work stress, mainly due to unsuitable work conditions, organizational factors within the family (e.g., working times, learning times of children, working times of cohabitants, and working times of other family members, etc. ), and the need to re-plan and re-organize work and family activities [30,31].…”
Section: Italian Schoolteachersmentioning
confidence: 99%
“…Teachers' well-being is a complex construct, which has been conceptualized as the absence of negative conditions such as teacher's stress, demotivation and even burnout (Huertas and Dávila, 2020 ; Bastías, 2021 ). Teachers' well-being has also been studied as it relates to coping strategies and engagement and recovery from work (Pöysä et al, 2021 ). From the perspective of Positive Psychology, well-being may be analyzed with a holistic approach such as Seligman's PERMA model (Seligman, 2012 ) as well as in eudaimonic dimensions such as the multidimensional psychological well-being model proposed by Ryff ( 1989 , 2014 ).…”
Section: Positive Psychology In Teachers' Well-beingmentioning
confidence: 99%